Mathematical model development of evacuated glass-thermal absorber tube Collector (EGATC) for air heating application - Zakaria, Zairul Azrul; Abdul Majid, Zafri Azran; Harun, Muhammad Amin; Ismail, Ahmad Faris; Ihsan, Sany Izan; Sopian, Kamaruzzaman; Abdul Razak, Amir; Sharol, Ahmad Fadzil; Mohd Azmi, Mohd Syahriman (UPSI Press, 2023)
For decades, solar energy as one of the endless energy sources has become the most public preference as a means to accommodate space heating. Various studies on solar thermal technologies have been worked out to replace outdated systems. However, conventional solar thermal systems offer two drawbacks such as diffuse solar radiation conditions that can lead to insufficient heating during winter and autumn, and limitations of the solar collector orientation that need to be opposed at a correct tilted angle towards maximizing the performance of the system. Previous studies have proposed an integrated design that consists of the evacuated tube and a preheating double-pass flow thermal absorber arrangement, namely, Evacuated GlassThermal Absorber Tube Collector (EGATC) to overcome these problems. Therefore, this research has discussed further on the formulated mathematical modeling of the design. EGATC components used to convert solar radiation into heat that stabilized and increased the outlet temperature were evacuated glass, thermal absorber, and working fluid. The equation related to each component was developed based on the first law of thermodynamics. The combination of the developed equations forms a solar thermal collector model for the system.